2020
DOI: 10.1007/s00062-020-00953-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurointervention in the 2020s: Where are We Going?

Abstract: The 1970s and 1980s-Discovery The history of neurointervention is short as our field is still in its puberty. If one had to pinpoint a starting date, most would agree it was the early 1970s, although Luessenhop and Spence described a case of an endovascular embolization of a brain arteriovenous malformation as early as 1960 [1]. The 1970s was the time when the pioneers of the field boldly went where no one had gone before. Their brilliant minds made huge advancements in the understanding of complex vessel anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 34 publications
3
67
0
Order By: Relevance
“…This finding has already been shown in the early time window for patients without revascularization treatment, 30 treated with intravenous thrombolysis 5 and with early EVT. 6,31,32 In our subgroup of patients admitted late and who had LVO (a minority of whom underwent EVT), we confirmed that a higher ASPECTS also remained independently associated with good clinical outcome, and we showed that the prognostic value of ASPECTS was similar to that of core volume on CTP. Nevertheless, relying on imaging alone could lead to erroneous outcome prediction.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This finding has already been shown in the early time window for patients without revascularization treatment, 30 treated with intravenous thrombolysis 5 and with early EVT. 6,31,32 In our subgroup of patients admitted late and who had LVO (a minority of whom underwent EVT), we confirmed that a higher ASPECTS also remained independently associated with good clinical outcome, and we showed that the prognostic value of ASPECTS was similar to that of core volume on CTP. Nevertheless, relying on imaging alone could lead to erroneous outcome prediction.…”
Section: Discussionsupporting
confidence: 77%
“…We included 1046 patients with a median age of 71.4 years (interquartile range, IQR ¼ 59.8-79.4 years), an NIHSS score of 12 (IQR,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), an ASPECTS of 9 (IQR, 7-10), and a CTP core of 13.6 mL (IQR, 0.6-52.8 mL). The overall correlation between ASPECTS and CTP core was moderate (r ¼ -0.49, P , .01) but significantly stronger in the late-versus-early window (r ¼ -0.56 and r ¼ -0.48, respectively; P ¼ .05) and in the presence versus absence of large-vessel occlusion (r ¼ -0.40 and r ¼ -0.20, respectively; P , .01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the time-savings for thrombolysis with tPA, MSUs can also optimize triage for other stroke patients, such as those with large vessel occlusions (LVO) and intracranial hemorrhage (ICH). Given evidence from clinical trials showing the powerful benefit of MT compared with standard medical management in improving clinical outcomes and disability of selected stroke patients with LVOs up to 24 hours, 6,7,[52][53][54] MSUs can be a conduit for providing patients with LVOs access to MT by directly transporting MT-eligible patients to thrombectomy capable stroke centers. Given the reduced chance of endovascular treatment for every minute of transfer delay from a nonendovascular center to a hospital capable of delivering such interventions, 55 MSUs can enhance the "time is brain" mantra by identifying, triaging, and transporting stroke patients with LVOs to hospitals with appropriate endovascular services by using CT angiography and/or perfusion on the MSU itself to identify salvageable penumbra and LVOs.…”
Section: Applications Beyond Thrombolysismentioning
confidence: 99%
“…S ince 2015, endovascular therapy (EVT) and intravenous alteplase as a combined treatment have been standard of care in patients with acute ischemic stroke with large-vessel occlusion (LVO) eligible for intravenous alteplase. 1 When the 5 major EVT trials were conducted, intravenous alteplase was the only approved treatment for acute ischemic stroke. 2 Hence, the only acceptable trial design from an ethical standpoint was to test EVT in combination with intravenous alteplase against standard medical treatment.…”
mentioning
confidence: 99%